Can we regulate Fintech? Challenges and approaches - Villafuerte Mendoza, José (2021)
Faced with the undoubted proliferation of FinTech companies in Peru and in the world, this article describes the current situation of the market in this field in order to explore the legal implications of this new type of company.In that order, it first analyze how the digital market has evolved in financial and insurance matters. In the same way, it warns of the specific risks of the growing FinTech industry. All of that, to be able to point out the challenges that governments face in order to regulate this matter. In addition, it exhibits various proposals from sectors of the academia for the regulation of the FinTech market. With all this, the author concludes by giving his opinion on the mentioned proposals and presents his own for the regulation of FinTech companies, developing three main stages of implementation.